Vessel Health and Preservation: The Right Approach for Vascular Access 2019
DOI: 10.1007/978-3-030-03149-7_19
|View full text |Cite
|
Sign up to set email alerts
|

Right Management and Flushing

Abstract: Peripheral and central vascular access devices are a fundamental and essential part of healthcare delivery, used extensively in hospital and community settings to meet the challenging and complex IV therapy requirements of the modern-day patient. For vascular access devices (VAD) to be a safe and effective tool for the administration of IV therapy, they must be reliable. Reliability in this context refers to optimal catheter function, demonstrated by the ease of flushing and aspirating, combined with an absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 67 publications
(216 reference statements)
1
7
0
Order By: Relevance
“…After infusion, the procedure "cleans" the infused drug from the catheter lumen, reducing the risk of contact between incompatible drugs, and removes the proteins in the catheter wall, thus preventing obstruction of long catheters. [1][2][3]6 The lack of compliance with good practice guidelines for catheter maintenance identified in the results of this study is corroborated by international studies. [21][22][23][24][25] In the case of PIVCs, an investigation with 76 Brazilian and Portuguese nurses evaluated the flushing procedure through an online questionnaire.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…After infusion, the procedure "cleans" the infused drug from the catheter lumen, reducing the risk of contact between incompatible drugs, and removes the proteins in the catheter wall, thus preventing obstruction of long catheters. [1][2][3]6 The lack of compliance with good practice guidelines for catheter maintenance identified in the results of this study is corroborated by international studies. [21][22][23][24][25] In the case of PIVCs, an investigation with 76 Brazilian and Portuguese nurses evaluated the flushing procedure through an online questionnaire.…”
Section: Discussionsupporting
confidence: 71%
“…The application of laminar flow, in turn, is performed with the administration of a continuous flow of the solution for washing the catheter. 1,2 Studies indicate that flushing with a pulsatile flow significantly reduces fibrin and other deposits compared to laminar flow; it is more efficient in removing fibrin and drug cement and, consequently, preventing catheter occlusion. 1,25 Also, one study demonstrated that pulsatile flow is at least twice as effective in reducing the number of colony-forming units per milliliter compared to a single 10-mL bolus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations